1989
DOI: 10.1121/1.397854
|View full text |Cite
|
Sign up to set email alerts
|

The measurement of loudness in individual children and adults by absolute magnitude estimation and cross-modality matching

Abstract: Twelve adults and 11 children (age range 4-7 years) performed absolute magnitude estimation of the apparent lengths of lines and the loudnesses of 1000-Hz tones as well as cross-modality matching between loudness and apparent line length. Consistent with the notion that children and adults have similar impressions of loudness, there were no major differences between the absolute magnitude estimation (AME) and cross-modality matching (CMM) data of the adults and children. A direct comparison between the exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
36
1
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 0 publications
7
36
1
2
Order By: Relevance
“…The obtained power of 0.99 was very close to 1.0, such as observed in studies in which such estimates of magnitudes are matched to line-length (13)(14) . The equivalence between the empirical and the predicted power, when two modalities are used, is an evidence of confirmation of Steven's Power Law (13) .…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The obtained power of 0.99 was very close to 1.0, such as observed in studies in which such estimates of magnitudes are matched to line-length (13)(14) . The equivalence between the empirical and the predicted power, when two modalities are used, is an evidence of confirmation of Steven's Power Law (13) .…”
Section: Discussionsupporting
confidence: 51%
“…Studies have used line-length, matching them to other modalities such as brightness and loudness and the found prediction was nearly perfect (14)(15) .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have studied the individual differences among subjects performing magnitude estimation. Ofparticular interest are the results ofCollins and Gescheider (1989), who found that the ME exponents for loudness and line length were correlated within a group of subjects (but see M. R. Teghtsoonian, 1971, 1983), so that the standard deviation of each exponent (adults: loudness-0.155, line length-0.582), was larger than the standard deviation of their ratio (loudness/line length-0.039).…”
Section: Discussionmentioning
confidence: 99%
“…The distortion is particularly apparent when one is measuring psychophysical functions for a modality by using magnitude estimation and magnitude production. The traditional practice is to estimate the unbiased exponent by taking the geometric mean of the ME and MP exponents (see, e.g., Collins & Gescheider, 1989 Finger Span (em) Figure 5. Cross-modal matching data from each subject in the second experiment ofthe present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation